2012
DOI: 10.1111/j.1939-1676.2012.01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Use in Horses Undergoing Colic Surgery

Abstract: Background: Recommendations for antimicrobial prophylaxis for surgery are well-described in human medicine, but information is limited for veterinary practice.Objective: To characterize antimicrobial use in horses undergoing emergency colic surgery. Animals: A total of 761 horses undergoing emergency colic surgery (2001)(2002)(2003)(2004)(2005)(2006)(2007). Methods: Retrospective case review. Antimicrobial dose and timing, surgical description, and duration of treatment were collected from medical records. Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 38 publications
(69 reference statements)
4
36
0
Order By: Relevance
“…The authors’ data are in agreement with data from other countries, supporting that similar concerns regarding antimicrobial prescribing practices are present in North America and Europe (Weese and Sabino 2005, Weese and Cruz 2009, Dallap Schaer and others 2012, Hughes and others 2013, De Briyne and others 2014). The frequency of selection of a CIA (European Medicines Agency 2014) was similar to a European-wide survey (De Briyne and others 2014).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…The authors’ data are in agreement with data from other countries, supporting that similar concerns regarding antimicrobial prescribing practices are present in North America and Europe (Weese and Sabino 2005, Weese and Cruz 2009, Dallap Schaer and others 2012, Hughes and others 2013, De Briyne and others 2014). The frequency of selection of a CIA (European Medicines Agency 2014) was similar to a European-wide survey (De Briyne and others 2014).…”
supporting
confidence: 86%
“…Extending the perioperative treatment is controversial as no beneficial effect of prolonged duration compared with single dose or no prophylactic administration could be shown (Borg and Carmalt 2013, Freeman and others 2012). This study and others indicate that excessive use of surgical antimicrobial prophylaxis is common in equine practice (Weese and Cruz 2009, Dallap Schaer and others 2012). …”
supporting
confidence: 63%
“…Horses receive perioperative antimicrobial therapy during emergency exploratory celiotomy due to the likelihood of the procedure being clean contaminated or contaminated, as well as the risk of pneumonia in horses that are anesthetized or shipped long distances to reach the hospital 67,68 . Suggested guidelines for antimicrobial prophylaxis in horses undergoing clean‐contaminated procedures include choosing a broad‐spectrum antimicrobial of lower generation (to minimize development of bacterial resistance), administration within 30–60 min of the initial incision, and re‐dosing intraoperatively if surgery exceeds 2 half‐lives of the preoperative dose 69 . A retrospective study at one institution reported frequent improper use of antimicrobial prophylaxis including inaccurate dosing, administration >60 min prior to surgery, and lack of re‐dosing when surgery time exceeded 2 half‐lives of the drug 69 .…”
Section: Introductionmentioning
confidence: 99%
“…Suggested guidelines for antimicrobial prophylaxis in horses undergoing clean‐contaminated procedures include choosing a broad‐spectrum antimicrobial of lower generation (to minimize development of bacterial resistance), administration within 30–60 min of the initial incision, and re‐dosing intraoperatively if surgery exceeds 2 half‐lives of the preoperative dose 69 . A retrospective study at one institution reported frequent improper use of antimicrobial prophylaxis including inaccurate dosing, administration >60 min prior to surgery, and lack of re‐dosing when surgery time exceeded 2 half‐lives of the drug 69 . This study reported a surgical site infection rate of 15.6% and suggested that some postoperative complications including surgical site infections may be reduced by using appropriate antimicrobial protocols 69 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation